The employer brand : bringing the best of brand management to people at work - Barrow, Simon (Wiley, 2005)
Levels of 'employer brand awareness' are rising fast across Europe, North America and Asia-Pacific, as leading companies realise that skilled, motivated employees are as vital to their commercial success as profitable customers and apply the principles of branding to their own organization. Starting with a review of the pressures which have generated current interest in employer branding, this definitive book goes on to look at the historical roots of brand management and the practical steps necessary to achieve employer brand management success - including the business case, research, positio.